Linking the association between circRNAs and Alzheimer’s disease progression by multi-tissue circular RNA characterization - Lo, IJu (RNA Biol, 2020)
Alzheimer’s disease (AD) has devastating consequences for patients during its slow, progressive course. It is important to understand the pathology of AD onset. Recently, circular RNAs (circRNAs) have been found to participate in many human diseases including cancers and neurodegenerative conditions. In this study, we mined the published dataset on the AMP-AD Knowledge Portal from the Mount Sinai Brain Bank (MSBB) to describe the circRNA profiles at different AD stages in brain samples from four brain regions: anterior prefrontal cortex, superior temporal lobe, parahippocampal gyrus and inferior frontal gyrus. In total, we found 147 circRNAs to be differentially expressed (DE) for different AD severity levels in the four regions. We also characterized the mRNA-circRNA co-expression network and annotated the potential function of circRNAs based on the co-expressed modules. Based on our results, we found that the most circRNA-regulated region in AD patients with severe symptoms was the parahippocampal gyrus. The strongest negatively AD severity-correlated module in the parahippocampal gyrus was enriched in cognitive disability and pathological-associated pathways such as synapse organization and regulation of membrane potential. Finally, a regression model based on the expression pattern of DE circRNAs in the module could help to distinguish the disease severity of patients, further supporting a role for circRNAs in AD pathology. In conclusion, our findings indicate that circRNAs in parahippocampal gyrus are possible biomarkers and regulators of AD as well as potential therapeutic targets.